The Evolution of the Continental Crust and the Onset of Plate Tectonics - Hawkesworth, Chris J.; Cawood, Peter A.; Dhuime, Bruno (Frontiers in Earth Science, 2020)
The Earth is the only known planet where plate tectonics is active, and different studies have concluded that plate tectonics commenced at times from the early Hadean to 700 Ma. Many arguments rely on proxies established on recent examples, such as paired metamorphic belts and magma geochemistry, and it can be difficult to establish the significance of such proxies in a hotter, older Earth. There is the question of scale, and how the results of different case studies are put in a wider global context. We explore approaches that indicate when plate tectonics became the dominant global regime, in part by evaluating when the effects of plate tectonics were established globally, rather than the first sign of its existence regionally. The geological record reflects when the continental crust became rigid enough to facilitate plate tectonics, through the onset of dyke swarms and large sedimentary basins, from relatively high-pressure metamorphism and evidence for crustal thickening. Paired metamorphic belts are a feature of destructive plate margins over the last 700 Myr, but it is difficult to establish whether metamorphic events are associated spatially as well as temporally in older terrains. From 3.8–2.7 Ga, suites of high Th/Nb (subduction-related on the modern Earth) and low Th/Nb (non-subduction-related) magmas were generated at similar times in different locations, and there is a striking link between the geochemistry and the regional tectonic style. Archaean cratons stabilised at different times in different areas from 3.1–2.5 Ga, and the composition of juvenile continental crust changed from mafic to more intermediate compositions. Xenon isotope data indicate that there was little recycling of volatiles before 3 Ga. Evidence for the juxtaposition of continental fragments back to ~2.8 Ga, each with disparate histories highlights that fragments of crust were moving around laterally on the Earth. The reduction in crustal growth at ~ 3 Ga is attributed to an increase in the rates at which differentiated continental crust was destroyed, and that coupled with the other changes at the end of the Archaean are taken to reflect the onset of plate tectonics as the dominant global regime.